A construção e o conflito de identidade em " Os Famosos e os Duendes da Morte”, de Ismael Caneppele - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2019)
An unnamed teenager boy who lives in a small town has his identity fragmented when he was struck by a shocking event in his life. The shock broke the monotonous daily provocations from his best friend telling him that he will never be able to set himself free from the small town way of life or from feeling out of place, from being isolated and non-existent in this place, so he tries to find a way out of there. One way out is in the virtual world where he can find similarity, acceptance and freedom when he chats with his virtual friends. He finds himself torn between one place and another, between the traditionalism of his city and the modernity of the big city observed by him through the virtual world. This anonymous teenager and his conflicting identity inhabit the novel Os famosos e os duendes da morte written by Ismael Caneppele, who also develops his art making movies and plays. In a text full of gaps, identity crisis, melancholy and Bob Dylan, Caneppele poetically built the four walls of a teenager’s life and his questions about his own existence trying to figure out the answers. The construction of the identity of the individual has excelled in several areas of knowledge, one of them can be found in literature. This project aims to analyse, in the novel Os famosos e os duendes da morte and also on its movie adaption both written by Ismael Caneppele, the construction of identity and the conflict between the traditional and the modern way of life based on theorists as Zygmunt Bauman (2005) and Stuart Hall (2006), due to the fact that Hall and Bauman explain how the identity of the individual is constantly being modifiable and giving new meaning to the reality which surrounds it. Both Caneppele’s works can be a setting for the dialectics between customs, which passed on from one generation to another, and habits that have been introduced recently into society such as the frequent use of the internet. His both works can also be associated to the hybridity of the individual’s identity, this type of hybridity comes from a meeting point between old customs and new habits, the fusion that exemplifies what Hall and Bauman say about the building oh the individual’s identity.
Keywords: Literatura; Identidade; Tradição; Literature; Identity; Tradition; CNPQ::LINGUISTICA, LETRAS E ARTES